Design as a performative agent: cultural mediation towards change and social benefit (Encuentros, 2025)
This article elaborates an approach to the interdisciplinary practices of Design, and also to the impact they can have on the thinking, emotions and attitudes of the people who are immersed in their daily spaces of interaction. Unveiling the benefits that artifacts achieve as a result of such practices, reveals a substance that transcends the universe of products, services, and experiences. In the face of these realities, Design projects the cultivation of behaviors that go beyond the political dimension of the economy, when it commits itself to the construction of values from its powerful social mediation. Aspects such as inclusion; the defense of human rights; respect for cultural diversity; freedom of otherness; preservation of environmental health; orientation and information in interactive spaces; education; and universal benefit, among other factors, are among its interests. However, the ever-changing cultural specificities, atomized in needs, aspirations, desires and lifestyles, tend, at times, not to correspond to the artifactual solutions due to the biased results resulting from traditional design methodologies. Therefore, this research integrates the above theories with the development of assertive tools to typify users, as well as heuristics for the evaluation of processes and results, applied to case studies of different nature. In this way, the role of Design can reach high levels of performativity, especially when it seeks to generate changes towards social benefit and transformation.
Keywords: Design; Performativity; Rhetorical; Evluation heuristics; Ideological agent; Design and education; Perception; Social conflict; Users